Study of Production Performance and Economic of Broiler Farms in Parwan Afghanistan - Zrawar, Multan; Rasikh, Mahmoodullah; Danishyar, Eraj; Motmain, Zekrullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
Poultry industry is one of the main source of income in Afghanistan, where about 1.5 million people are engaged in this sector. In recent years, from 476 poultry farms only 165 farms are continuing their activities in Parwan province of Afghanistan, which means that most of previous farms are broken down. In this research, 30 broiler chicken farms were selected by random sampling method and to evaluate the production performance and economical status of broiler farms in Parwan, Afghanistan. Data were collected by using questionaries’ and personal interviews. Based on the results, it was found that the production performance of the chickens was such as the feed conversion ratio was 1.83, the livability percentage was 90.23%, the average market weight was 1.9 kg, and the mortality rate was 9.77%. The fixed costs included 5.64% worker's salary, 0.79% farm rent and 0.32% electricity bill which are totally (6.75%). Variable costs include the cost of a day-old chicken 6.98%, feed cost 70.45%, veterinary service cost 3.44%, litter cost 1.41%, worker food cost 2.11%, fuel cost 7.05% and miscellaneous cost were 1.47%, which totally reached (93.25%). The total income which were earned 97.93% from live chickens as main product and 2.07% from manure as by product and the benefit cost ratio was 1.07%. To conclude this, as the broiler production is profitable, but the proportion of income is less than the investment. In order to improve the income, it is recommended to provide high-quality feed, prevent diseases, providing high-quality vaccines and medicines, and hiring experts in broiler farms.